2021
DOI: 10.3389/fped.2021.658845
|View full text |Cite
|
Sign up to set email alerts
|

Using MEST-C Scores and the International Study of Kidney Disease in Children Classification to Predict Outcomes of Henoch–Schönlein Purpura Nephritis in Children

Abstract: Introduction: Henoch–Schönlein purpura nephritis (HSPN) and IgA nephropathy (IgAN) bear similarities in some aspects. The histological classification of HSPN was built on the International Study of Kidney Disease in Children (ISKDC) criteria, while IgAN was established on the 2016 Oxford classification (MEST-C scores). The purpose of this paper was to discuss the predictive value of the ISKDC classification and MEST-C scores in children with HSPN.Methods: We performed a retrospective study of 877 children with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…The researchers pointed out that the updated Oxford classification is applicable to IgAVN, both in children and adults, and may also aid in disease management and kidney outcome prediction of IgAVN ( 3 , 44 ). Wang et al ( 45 ) found that the S and T of Oxford classification can be used to predict the renal prognosis of IgAVN children.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers pointed out that the updated Oxford classification is applicable to IgAVN, both in children and adults, and may also aid in disease management and kidney outcome prediction of IgAVN ( 3 , 44 ). Wang et al ( 45 ) found that the S and T of Oxford classification can be used to predict the renal prognosis of IgAVN children.…”
Section: Discussionmentioning
confidence: 99%
“…Clavé et al (21) studied 170 children with biopsy-proven IgAVN diagnosed between 2007 and 2017, with patients with NS at presentation and those with cellular crescents and chronic lesions at initial renal biopsy being more likely to develop renal damage, highlighting the relationship between clinical and histological manifestations of IgAVN and factors affecting renal regression. In a retrospective study published in 2021, Wang et al discussed the predictive value of ISKDC classification and MEST-C scores on the prognosis of 877 children with IgAVN and found that S and T could be used to predict renal prognosis (22). However, the impact of renal pathological alterations on IgAVN remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, ISKDC is currently the most widely used classification for HSPN and mainly focus on active inflammation which is reflected by crescents formation. Increasing studies argue that the 2016 revised Oxford classification (MEST-C scores) should be recommended for children and adult patients with HSPN (18,32,33). Segmental glomerulosclerosis/adhesion (S) and tubular atrophy/interstitial fibrosis (T), which are not emphasized or included in ISKDC classification, are shown to be the prognostic factor for renal outcomes in those studies.…”
Section: Discussionmentioning
confidence: 99%